In vitro and molecular docking of α-Glucosidase inhibitor potency from Artabotrys suaveolens leaf and stem bark - Rosa, Dela; Elya, Berna; Hanafi, Muhamad; Khatib, Alfi (IOP Publishing, 2022)
Artabotrys suaveolens is one of the species from Artabotrys genus, one of the largest genus from Annonaceae family. This plant has been used traditionally to treat several diseases and also as emmenagogue. This research was aimed to explore the potency of Artabotrys suaveolens`s leaf and stem bark extracts as α-glucosidase inhibitor using in vitro and molecular docking techniques. It was found that IC50 of α-glucosidase inhibition activity of leaf extract was 48.18±0.16 ppm while the one of stembark extract was 44.99±0.35 ppm. Besides that, it was also found that IC50 of DPPH free radical scavenging activity of leaf extract was 114.074 ppm and of stem bark extract was 63.640 ppm. Further analysis indicated that α-glucosidase inhibition activity had stronger relationship with antioxidant activity in leaf extract compared to that in stem bark extract. Using LC-MS/MS, 23 compound structures were identified from leaf and stem bark extracts which were then analyzed using simulations of molecular docking to α-glucosidase receptor. The molecular docking results showed that several compounds both from leaf and stem bark extracts had good affinities to α-glucosidase receptor.